Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
[tex]\frac{n-6}{3n} = \frac{n-5}{3n+1} \\\\\frac{n-6}{3n} - \frac{n-5}{3n+1} = 0\\\\\frac{(3n+1)(n-6)-3n(n-5)}{3n(3n+1)} = 0\\\\(3n+1)(n-6)-3n(n-5) = 0\\\\3n^2-18n+n-6-3n^2+15n=0\\\\3n^2-3n^2-18n+n+15n-6=0\\\\-2n-6=0\\\\2n+6=0\\\\2n=-6\\\\n=-3[/tex]
You can solve this equation by applying the zero product rule.
Firstly, you equate the expression to 0 in order to combine both fractions into one. As shown in Step 2, you find the LCM of both fractions and multiply accordingly. In this case, the LCM of both fractions is 3n(3n+1). Hence you cross multiply.
Next, you eliminate the denominator in order to solve the equation more conveniently. As you multiply the fraction by the denominator on the LHS, you do that to the RHS as well to maintain balance. 0×3n(3n+1)=0, hence Step 3.
Then, you expand the parentheses using the distributive law of multiplication, resulting in a quadratic equation.
Lastly, you solve the quadratic equation.
The answer is n=-3
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.